Analysis of 20% human albumin prescriptions from a teaching hospital and their respective expense description (Research, Society and Development, 2023)
Albumin is the most important plasma expander in the bloodstream. In the form of medication, it must be prescribed after a thorough evaluation of the patients, basing its use according to the literature, as it has contraindications, such as bleeding in post-surgical patients, in addition to being a high-cost medication. Thus, the objective of this work was to carry out a survey of the therapeutic indications contained in the prescriptions of human albumin (HA) 20% of a Teaching Hospital in the city of Recife, Pernambuco, Brazil, in order to assess whether such indications have scientific basis, in addition to a survey of the costs related to the acquisition of this drug should be carried out. A cross-sectional, retrospective study was carried out, based on the analysis of prescriptions prescribed to patients, from May 2015 to May 2017. The therapeutic indications found were: relief paracentesis (29%), hepatorenal syndrome (HRS) (22,9%), hypovolemia (20.6%), septic shock (8.7%), spontaneous bacterial peritonitis (SBP) (6.4%), hypoalbuminemia (6.1%), ascites (4.1%), neoplasia (1.2%) and hepatic encephalopathy (HE) (0.6%). After a literature review, HA 20% has scientific support for the treatment of paracentesis, SHR and PBE, which corresponds to 63.1% of prescriptions and has no scientific support for the treatment of hypovolemia, septic shock, hypoalbuminemia, cancer and HE (36.9%), which can be replaced by other plasma expanders. Thus, the importance of basing the prescription of 20% HA according to the literature is highlighted, always aiming at the rational use of medicines.